Green Euphoria: Unraveling the Power of Sustainable Brands - Examining the Nexus of Green Brand Image, Authenticity, and Emotional Well-being with the Mediating Force of Green Brand Attachment - Manisa Khoirala, Cindy; Alfansi, Lizar (Journal of Entrepreneurship and Business, 2024)
Pupose: The study intends to examine the indirect relationship between green brand image and green brand authenticity on consumer emotional well-being through the mediating variable of green brand attachment. Method: This study employs a quantitative-explanatory approach to examine the relationships between variables. The research focuses on consumers of environmentally friendly cosmetic products in Indonesia. The analysis utilized in this study is Structural Equation Modeling based on Partial Least Squares. The exact number of respondents analyzed in this research is 300 individuals who use environmentally friendly cosmetic products in Indonesia. Result: The findings of this research indicate that Green Brand Authenticity (GA) and Green Brand Image (GBI) have a positive impact on Consumer Emotional Well Being (CWB). Similarly, Green Brand Authenticity (GA) and Green Brand Image (GBI) positively influence Green Brand Attachment (GBA). Green Brand Attachment positively affects Consumer Emotional Well Being (CWB). Green Brand Attachment (GBA) plays a partial mediating role in accommodating the relationship between Green Brand Authenticity (GA) and Green Brand Image (GBI) with Consumer Emotional Well Being (CWB).